2018
DOI: 10.1073/pnas.1717948115
|View full text |Cite
|
Sign up to set email alerts
|

The eardrums move when the eyes move: A multisensory effect on the mechanics of hearing

Abstract: Interactions between sensory pathways such as the visual and auditory systems are known to occur in the brain, but where they first occur is uncertain. Here, we show a multimodal interaction evident at the eardrum. Ear canal microphone measurements in humans (n = 19 ears in 16 subjects) and monkeys (n = 5 ears in three subjects) performing a saccadic eye movement task to visual targets indicated that the eardrum moves in conjunction with the eye movement. The eardrum motion was oscillatory and began as early a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
61
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 78 publications
(110 reference statements)
10
61
1
Order By: Relevance
“…A recent study in humans by Gruters et al, 2018 , showed a close relationship between movements of the left and right eardrums and multiple parameters of task-related left- and right-directed eye movements. It will be important in future research to test whether muscular responses of the middle and outer ears are linked in a coordinated manner to ocular orienting.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study in humans by Gruters et al, 2018 , showed a close relationship between movements of the left and right eardrums and multiple parameters of task-related left- and right-directed eye movements. It will be important in future research to test whether muscular responses of the middle and outer ears are linked in a coordinated manner to ocular orienting.…”
Section: Discussionmentioning
confidence: 94%
“…Besides anatomical studies, recent magnetoencephalographic studies investigating predictions in auditory scenes in humans found significant effective connectivity from motor cortex toward auditory areas ( Abbasi and Gross, 2020 ; Morillon and Baillet, 2017 ). In addition, besides direct projections, an indirect source of motor influences on the auditory system could stem from the cochlea, as a recent study reported oscillations of the eardrum coinciding with saccade onset in the absence of sound ( Gruters et al., 2018 ). The authors hypothesized that the eardrum movement is due to a copy of the motor command that generates saccades.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gruters et al ( 2018 ) found an interaction between saccadic eye movement and changes in ear-canal sound pressure that lasted for 10’s of ms. The infrasounds produced by such eye movements would have been filtered out in our measurements, but they do point out that there are many subject motion changes that may affect ear-canal noise.…”
Section: Discussionmentioning
confidence: 99%